Cats Toxoplasmosis Control in Indonesia - Ageng Ilham Ramadhani; R Yesica; IB GR Wisesa (Indonesian Center for Animal Research and Development, 2022)
Toxoplasmosis is one of the parasitic diseases caused by Toxoplasma gondii (T. gondii). Toxoplasma gondii is usually found in cats’ faeces, raw vegetables, meats, grasses, and soil. The transmission of T. gondii happens vertically or horizontally. The standard diagnostic techniques of T. gondii detection are microscopic examination of cats faeces, PCR, and antibody detection. The drug of choice in cats toxoplasmosis is clindamycin antibiotic (doses: 10-12/kgBW), another treatment is the combination of sulfadiazine 120 mg/kgBW dan pirimetamin 1 mg/kgBW also can be given to reduce the oocyst shed. The prevention of T. gondii infection in cats is not giving raw meats and keeping the environment disinfected. The prevalence of cats toxoplasmosis in cats in Indonesia is influenced by multiple diagnostic techniques, sample total, geographical condition, and climate. The risk factor of toxoplasmosis infection in cats are stray cats, raw foods, and a hygienic environment. The purpose of this article is knowing the life cycle of T. gondii, clinical sign, pathogeneses, diagnostic method, risk factors, control, and the prevalence of cats toxoplasmosis in Indonesia in the last 50 years.